Réponses

  • Omnes
  • Modérateur confirmé
2014-03-04T22:35:15+01:00
Salut,

 A(x) = ( 4x - 7) ( 2x + 3) + ( 2x + 3) ²
A(x) = 8x² + 12x - 14x - 21 + 4x² + 12x + 9
A(x) = 12x² +10x -12

 A(x) = ( 4x - 7) ( 2x + 3) + ( 2x + 3) ²
A(x) = ( 4x - 7) ( 2x + 3) + ( 2x + 3) ( 2x + 3)
A(x) = (2x+3)[4x - 7 + 2x + 3]
A(x) = (2x+3)(6x -4)
A(x) = 2(2x+3)(3x-2)

A(x) = 0
2(2x+3)(3x-2) = 0
(2x+3) = 0
2x = -3
x = -3/2

3x -2 = 0
3x = 2
x = 2/3

Bonne soirée!


2014-03-04T22:58:54+01:00
A(x) = ( 4x - 7) ( 2x + 3) + ( 2x + 3) ² 1.    

Développer et réduire A (x).

(8x²+12x-14x-21) + ( 2x + 3) ( 2x + 3)
(8x²-2x-21) + (4x²+6x+6x+9)
(8x²-2x-21) + (4x²+12x+9)
12x²+10x-12  

2.     Factoriser A (x).
( 4x - 7) ( 2x + 3) + ( 2x + 3) ( 2x + 3)
( 2x + 3) [ (4x-7)+ ( 2x + 3) ]
( 2x + 3) [ (6x-4) ]   

3.     Résoudre l'équation A (x) = 0.
( 4x - 7) ( 2x + 3) + ( 2x + 3) ² = 0
Prenons cette écriture à ( 2x + 3) [ (6x-4) ]
 ( 2x + 3) =0        ET          (6x-4) = 0
2x = -3                ET           6x=4
X= - 3/2                 ET            X= 4/6 = 2/3
Donc Solution = [ -3/2 ; 2/3 ]
Voilà aime si ça t'a aidé :)